2020
DOI: 10.1038/s42003-020-0996-z
|View full text |Cite
|
Sign up to set email alerts
|

Quassinoid analogs with enhanced efficacy for treatment of hematologic malignancies target the PI3Kγ isoform

Abstract: Development of novel PI3K inhibitors is an important strategy to overcome their resistance and poor tolerability in clinical trials. The quassinoid family member Brusatol shows specific inhibitory activity against hematologic malignancies. However, the mechanism of its anti-cancer activity is unknown. We investigated the anti-cancer activity of Brusatol on multiple hematologic malignancies derived cell lines. The results demonstrated that the PI3Kγ isoform was identified as a direct target of Brusatol, and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Similar results have also been found in NPC (CNE-1), with a decrease in cyclin B1, cyclin D1, Cdc2, and Cdc25c, and an increase in p-Cdc2; the cells also are arrested in only one phase [60]. In other cancer types, brusatol exerts an anti-proliferative effect by interfering with the cell cycle, including G0/G1 phase in the PC9 and HCC827GRKU lung cancer cell lines [21,54], and the Raji and SU-DHL-4 lymphoma cell lines [45], and G2/M phase in the pancreatic cancer lines Capan-2 and PANC-1 [63]. In A375 melanoma cells, Wang et al have found that cyclin D1, cyclin E2, CDK4 and CDK6 decrease after brusatol treatment, thus causing G0/G1 cell-cycle arrest [67].…”
Section: Cell-cycle Arrestmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results have also been found in NPC (CNE-1), with a decrease in cyclin B1, cyclin D1, Cdc2, and Cdc25c, and an increase in p-Cdc2; the cells also are arrested in only one phase [60]. In other cancer types, brusatol exerts an anti-proliferative effect by interfering with the cell cycle, including G0/G1 phase in the PC9 and HCC827GRKU lung cancer cell lines [21,54], and the Raji and SU-DHL-4 lymphoma cell lines [45], and G2/M phase in the pancreatic cancer lines Capan-2 and PANC-1 [63]. In A375 melanoma cells, Wang et al have found that cyclin D1, cyclin E2, CDK4 and CDK6 decrease after brusatol treatment, thus causing G0/G1 cell-cycle arrest [67].…”
Section: Cell-cycle Arrestmentioning
confidence: 99%
“…Pei et al have reported that brusatol arrests cells at G0/ G1 phase in vitro and suppresses cancer growth in vivo [45]. Mata-Greenwood et al have shown that brusatol induces leukemic cell differentiation and G1 cell-cycle arrest, which are associated with the downregulation of c-myc [48].…”
Section: Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Since Eph and ephrins have a remarkable role in infectious diseases it has been increasingly recognized as an attractive therapeutic target for many diseases which includes anticancer therapeutics, synaptic plasticity modulators, homeostasis of bone, and the stem cell biology [ 21 , 116 , 155 ]. Most of the kinase inhibitors possess poor selectivity and target multiple kinases.…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…This may further inhibit TGF-β1 (transforming growth factor beta 1) mediated apoptosis and promote cell survival for lymphomagenesis [ 12 ]. Our recent study demonstrated that PI3Kγ is a potential target of Brusatol and its derived analogs in EBV-positive lymphomas [ 13 ]. Additionally, other important WNT and MAPK (mitogen-activated protein kinase) signaling pathways are also hijacked by EBV latent proteins to exhibit hallmarks of cancer during lymphomagenesis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%